The structure of menopausal syndrome: Using network analysis to understand unique symptomatic relationships. Issue 1 (31st July 2022) - Zhao, Di; Lv, Gaorong; Qi, Meiling; Xie, Zihui; Zhang, Yunxue; Zhou, Miao; Wang, Qing; Li, Ping
Abstract: Objective: To explore the network structure underlying the symptoms of menopausal syndrome and to identify the central and bridge symptoms of menopause among middle‐aged women. Methods: This is a cross‐sectional survey study conducted in the Chinese community with a total of 1829 women aged 40–65 years. The Menopause Rating Scale (MRS) was used to assess the menopausal syndrome, including somato‐vegetative, psychological, and urogenital subdomains. The network analysis was performed to determine the central and bridge symptoms of menopause. Results: In the network of menopausal symptoms, anxiety, vaginal dryness, depressive mood, and irritability were the most central symptoms. Depressive mood, anxiety, and vaginal dryness were also detected as the bridge symptoms. The estimated network between the symptoms had good stability (CS‐strength = 0.75 and CS‐edge = 0.75). Conclusion: The present network analysis provided unique insights into the inner structure of menopausal symptoms. Psychological symptoms should be considered as the core symptoms in developing relevant interventions to improve the health and well‐being of middle‐aged women. Synopsis: Anxiety, vaginal dryness, depressive mood, and irritability are the central symptoms of menopausal syndrome among middle‐aged women.